2014
DOI: 10.1186/1477-7819-12-59
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up study of unilateral renal function after nephrectomy assessed by glomerular filtration rate per functional renal volume

Abstract: BackgroundTo evaluate the clinical usefulness of estimated glomerular filtration rate (eGFR) divided by functional renal volume (FRV) measured by three-dimensional image reconstruction (eGFR/FRV) for the prediction of functional outcomes after nephrectomy.MethodsEighty-three patients who underwent nephrectomy were enrolled. The FRV of each patient was measured before surgery. Preoperative medical information on proteinuria, blood pressure, blood glucose level, body mass index (BMI), hemoglobin level and serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
(32 reference statements)
0
19
0
1
Order By: Relevance
“…24,25 Hosokawa et al assessed preoperative GFR per unit of functional renal volume and found it was a causative factor for postoperative proteinuria. 26 However, they did not estimate postoperative GFR per unit of functional renal volume, and the cohorts did not distinguish between patients who had undergone donor nephrectomy, nephroureterectomy and RN for RCC, precluding appropriate appraisal of the usefulness of GFR per unit of functional volume. Nevertheless, in the present study we estimated renal volume before and after surgery, and assessed the GFR/FRV to evaluate the degree of compensatory functional adaptation 1 year after RN.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Hosokawa et al assessed preoperative GFR per unit of functional renal volume and found it was a causative factor for postoperative proteinuria. 26 However, they did not estimate postoperative GFR per unit of functional renal volume, and the cohorts did not distinguish between patients who had undergone donor nephrectomy, nephroureterectomy and RN for RCC, precluding appropriate appraisal of the usefulness of GFR per unit of functional volume. Nevertheless, in the present study we estimated renal volume before and after surgery, and assessed the GFR/FRV to evaluate the degree of compensatory functional adaptation 1 year after RN.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral nephrectomy is a major surgery indicated for kidney donation 1 or conditions that lead to poorly functioning or nonfunctioning kidney as renal cell or urothelial cancer. 2 After unilateral nephrectomy, the remaining kidney undergoes structural and functional changes as a pliant response to quench the increased functional demand to maintain the homeostasis of fluid and solutes in the body.…”
Section: Introductionmentioning
confidence: 99%
“…This may suggest that patients with low FT3 levels are hypervolemic and through secondary inhibition of the RAS system, they are prone to be hyperkalemic. Nephrectomy is a risk factor for CKD development and even in healthy individuals with donor nephrectomy, progression to end-stage renal disease (ESRD) is possible both after indication and donor nephrectomy; basically the renal residual volume but also age, obesity and the presence of co-morbid conditions such as diabetes and hypertension are important for predicting the progression of renal disease (9)(10)(11)25). However, in these patients, the effect of thyroid function on renal outcome is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients; hypertension, proteinuria, obesity and metabolic syndrome are major risk factors for CKD progression and electrolyte abnormalities including hyperkalemia are common (9,11). However, the impact of thyroid dysfunction on CKD progression is not clear.…”
Section: Introductionmentioning
confidence: 99%